2021
DOI: 10.1248/bpb.b20-00576
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effects of Water-Soluble Extracts of Coarse and Fine Atmospheric Particulate Matter on Mast Cell Lines

Abstract: Fine particulate matter (PM 2.5 ) pollution causes serious health disorders, because PM 2.5 becomes deposited in the tracheobronchial and alveoli regions. In the extrathoracic region, there are more deposits of coarse particulate matter than fine particulates. As adverse health issues caused by coarse particulates have not been well investigated, this study examined the cytotoxicity of water-soluble extracts of both fine (0.05-3 µm, PM 0.05-3 ) and coarse (> 3 µm, PM >3 ) particulates collected from April 2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
(30 reference statements)
0
3
0
1
Order By: Relevance
“…Jin et al [ 38 ] suggested that PM may affect mast cell activation in a study using bone-marrow-derived mast cells. Kataoka et al [ 39 ] investigated the cytotoxic effects of water-soluble extracts of coarse and fine atmospheric PM on mast cell lines. Wang et al reported that PM 2.5 promotes the IgE-mediated mast cell activation of ROS [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jin et al [ 38 ] suggested that PM may affect mast cell activation in a study using bone-marrow-derived mast cells. Kataoka et al [ 39 ] investigated the cytotoxic effects of water-soluble extracts of coarse and fine atmospheric PM on mast cell lines. Wang et al reported that PM 2.5 promotes the IgE-mediated mast cell activation of ROS [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…大気中に浮遊する粒径が 2.5 µm 以下の粒子は, 呼吸器の奥深く肺胞まで到達し,血中への移行を 通じた重篤な健康被害をもたらす.例えば,慢 性 閉 塞 性 肺 疾 患(chronic obstructive pulmonary disease: COPD) 1) などの呼吸器系,院外心原性心停止 (out-of-hospital cardiac arrest: OHCA) 2,3) などの循環 器系及びアレルギー性鼻炎 4) などの免疫系,更に肺 がん 5) のような発がん性など多くの健康影響 [6][7][8] が 報告されている.大気粒子状物質は,発生源から直 接排出される一次粒子[有機炭素(有機化合物) ,元 素状炭素,無機元素(金属)など]と排出時にはガ ス状物質であるが,それらの化学反応により粒子化 される二次生成粒子(硫酸塩,硝酸塩,アンモニウ ム塩,低分子有機酸 9) など)が知られている. [10][11][12] 浮 遊 粒 子 状 物 質(suspended particulate matter: 18,19) その結果,硫酸アンモニウム は,細胞障害性を誘発し, 18) また,細胞障害を引き 起こさない条件で C57 細胞の脱顆粒を誘発,又は thapsigargin の刺激による脱顆粒反応を増強するこ とを報告した. 19) さらに,それらに影響するイオン は,硫酸アンモニウムの構成成分のうち,硫酸イオ ンではなくアンモニウムイオンであることを明らか にした. 18,19) ついで,われわれは中国大陸から PM 2. の培養条件を一部改良して行った.すなわち, ( 1)…”
Section: 緒 言unclassified
“…A mouse model demonstrates that fine particulate matter facilitates IgE-mediated mast cell degranulation and increased cytokine expression [42]. Investigating the cytotoxic effects of water-soluble extracts from fine and coarse particulate matter on mast cell lines, others show that both quantity and quality of particulate are implicated in severe tracheobronchial and alveolar illness [43].…”
Section: Social and Environmental Bases Of Mast Cell Disordersmentioning
confidence: 99%